2016
DOI: 10.5535/arm.2016.40.2.279
|View full text |Cite|
|
Sign up to set email alerts
|

Survey of Botulinum Toxin Injections in Anticoagulated Patients: Korean Physiatrists' Preference in Controlling Anticoagulation Profile Prior to Intramuscular Injection

Abstract: ObjectiveTo evaluate Korean physiatrists' practice of performing intramuscular botulinum toxin injection in anticoagulated patients and to assess their preference in controlling the bleeding risk before injection.MethodsAs part of an international collaboration survey study, a questionnaire survey was administered to 100 Korean physiatrists. Physiatrists were asked about their level of experience with botulinum toxin injection, the safe international normalized ratio range in anticoagulated patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Studies by Gertken et al, Boon et al, and Lynch et al for EMG notably tolerated wider and higher upper limit of INR, ranging from 1.2 to 4.2, 1.6 to 4.0, and 1.5 to 4.2, respectively 8‐14 . On the other hand, studies within the botulinum toxin cohort denoted a narrower and lower limit of INR range of 2 to 3 7,11‐16 …”
Section: Results Relating To Periprocedural Anticoagulant Managementmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies by Gertken et al, Boon et al, and Lynch et al for EMG notably tolerated wider and higher upper limit of INR, ranging from 1.2 to 4.2, 1.6 to 4.0, and 1.5 to 4.2, respectively 8‐14 . On the other hand, studies within the botulinum toxin cohort denoted a narrower and lower limit of INR range of 2 to 3 7,11‐16 …”
Section: Results Relating To Periprocedural Anticoagulant Managementmentioning
confidence: 94%
“…For practitioners who chose to use any of the three modalities for BTX, practice patterns on their choice of modality were vastly varied 16 . In one survey study, 5% of participating physicians mentioned the use of US guidance only for deep muscles in BTX procedure, whereas 36% will use portable electrical stimulation or EMG 15 . In the non‐survey group of studies, only two studies specifically mentioned the use of either or all of these three modalities as procedural guidance 11,13 …”
Section: Results Relating To Procedural Guidance For Btxmentioning
confidence: 99%
“…Intramuscular injections may result in local bleeding, especially in patients receiving anticoagulant therapy [9,10]. In particular, concerns have been raised about the potential for multiple intramuscular injections into deep compartmentalized muscles to cause acute compartment syndrome [11,12]. Limited information is available regarding the safety of intramuscular medications in patients receiving oral anticoagulants even though anticoagulants are commonly used, for example, in stroke patients as a prophylaxis for recurrent stroke [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys of physicians in Korea and Canada revealed considerable variability in physician practices and preferences when injecting botulinum toxin in anticoagulant-treated patients with spasticity, especially with regard to their comfort level using international normalized ratio (INR) ranges [11,12]. For example, in the Korean survey, 23% of the respondents indicated that they were uncertain whether they should inject patients with botulinum toxin without knowing the INR values, and 69% of the respondents reported that they did not have any standardized protocols for performing botulinum toxin injections in patients who were receiving anticoagulants [11]. The absence of clear information regarding bleeding risks and INR values associated with the injection of botulinum toxin in these patients contributes to physician uncertainty and to the wide range of approaches related to botulinum toxin injections in this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this emerging small body of evidence, many practitioners remain uncertain as to how to safely administer intramuscular chemodenervation injections to anticoagulated patients with the least disruption to their anticoagulation therapy. A recently published survey concluded that there is a lack of consensus in performing intramuscular botulinum toxin injections in anticoagulated patients, and emphasized the need for formulating a proper international consensus on botulinum toxin injection management in anticoagulated patients [22].…”
Section: Introductionmentioning
confidence: 99%